Chemical modelling of urine - Little, John Charles (Department of Chemistry, 2023)
A urine model has been developed. The model is used in the computation of chemical speciation and degree of precipitation by means of equilibrium constants and solubility products. The urine model was developed in order to investigate some of the factors associated with urolithiasis. A specific model development procedure was used. This procedure was based on iterative construction, validation, refinement and usage of the model. One refinement stage involved the potentiometric characterisation of the solution equilibria of the Mg-P0 4-NH 3-H system. Whereas the subsystems; H-P0 4 , H-NH 3 and Mg-P0 4 -H, were rigorously characterised, the overall system was only tentatively explored. The results obtained, however, indicate that the characterisation of the three subsystems is likely to be sufficient for the purposes of the urine model. The validation of the basic urine model was achieved by comparing the model's predicted precipitation with experimental observations in another project currently being pursued in this department. This validation has indicated that the kinetics of precipitation should be taken into account for some of the important urinary so 1 id. The urine mode 1 was nevertheless successfully used to investigate the effect of pH on urinary precipitation, the influence of some urinary components on calcium oxalate precipitation and the role of cadmium in urolithiasis. The results obtained were in general agreement with other observed and predicted results. Finally, a coherent procedure for investigating the problems of urolithiasis by means of such a model is proposed.